2016
DOI: 10.1016/j.yexmp.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Wnt/β-catenin signaling suppresses bleomycin-induced pulmonary fibrosis by attenuating the expression of TGF-β1 and FGF-2

Abstract: Pulmonary fibrosis is a progressive lung disorder of unknown etiology, which is characterized by alterations in alveolar epithelium function, fibroblast activation, and increased extracellular matrix deposition. Recent studies have demonstrated that PF is associated with uncontrolled production of cytokines after lung injury. In the present study, we found that transforming growth factor-β1 (TGF-β1) and fibroblast growth factor 2 (FGF-2) were both upregulated in bleomycin-induced fibrotic lung tissue and prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 45 publications
4
45
0
Order By: Relevance
“…Previous studies showed that bFGF and TGF-β1 play crucial roles in EMT and fibrosis [27,28]. Consistent with previous studies, our data also show that the cell morphology of bFGF-or TGF-β1-treated A549 cells was more scattered, slender and fibroblast-like (Figure 2A).…”
Section: Both Bfgf and Tgf-β1 Promoted Emt In A549 Cellssupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies showed that bFGF and TGF-β1 play crucial roles in EMT and fibrosis [27,28]. Consistent with previous studies, our data also show that the cell morphology of bFGF-or TGF-β1-treated A549 cells was more scattered, slender and fibroblast-like (Figure 2A).…”
Section: Both Bfgf and Tgf-β1 Promoted Emt In A549 Cellssupporting
confidence: 92%
“…Among the numerous pulmonary fibrosis/EMT models, the most common and successful model is bleomycin-induced pulmonary fibrosis/EMT, both in vivo and in vitro [17,24,36]. Previous studies verified that BLM can induce EMT of A549 cells via the TGF-β1/Smad signaling pathway and can increase the expression of bFGF and TGF-β1 [28]. In our results, the BLM-induced pulmonary fibrosis model was displayed by histology and immunohistochemistry staining.…”
Section: Pulmonary Fibrosis Inducer Bleomycin Regulates Esrp By Incsupporting
confidence: 62%
“…New studies showed that lncRNAs act as key ceRNAs [ 14 , 23 , 24 ], thereby greatly enhancing the functionality of lncRNAs. In the present study, we demonstrated that XIST inversely regulated miR-139 expression by directly binding; in addition, β-catenin, an essential factor in Wnt/β-catenin signaling which has been reported to play a promotive role in PF [ 25 27 ], could directly bind to miR-139 on an almost identical binding site. These data suggested that XIST might compete with β-catenin for miR-139 binding during PF progression so as to repress the inhibitory effect of miR-139 on β-catenin, which inspired us to further investigate the detailed function of miR-139 in PF.…”
Section: Discussionsupporting
confidence: 53%
“…Of note, Wnt/ β -catenin pathway blocking-mediated attenuation of bleomycin-induced PF was accompanied by a decreased expression of TGF- β 1 and fibroblast growth factor (FGF) 2 in vitro and in vivo. These results support that controlling the aberrant expression of TGF- β 1 and FGF2 via inhibition of Wnt/ β -catenin signaling could serve as a potential therapeutic strategy for PF [71]. Collagen triple helix repeat containing 1 (CTHRC1) protein showed the potential to inhibit Smad2/3 activation and alleviate bleomycin-induced fibrosis in mice [105].…”
Section: Wnt Signaling Pathways As Targets For Copd and Ipf Treatmmentioning
confidence: 61%